Augmented reality an economical solution for engineers and designers - Sidra Nasir; Mohammad Noman Zahid; Talha Ahmed Khan; Kushsairy Kadir; Sheroz Khan (Institute of Advanced Engineering and Science, 2020)
Now a days, with obscene workload and a busy life, many experts face problems which more or less result in loss of their customers or to certain overheads that immobilize the customer's satisfaction process. The software being proposed will facilitates professional from various field like in mechanical designing, interior designing and that of architects. This research proposal most likely acts as an effective tool that can reduce the gap between industrial enterprises and customers in addition to other relevant business groups. It helps to visualize architectural designs and interior designs. Before the physical implementation, a virtual model of a real environment can be designed, enabling designers to virtually implement their idea in the given workspace and then view it in a real environment, enabling designers to view their 3D visualizations on their 2D drawings this help them to initially visualize and reconstruct the design without wasting a large amount of money making it a cost-effective solution. Application is based on my observations of the user's aspirations of an augmented reality in design service, a service that combines different social media functionality, augmented reality (AR) and 3-D modeling that embraces the concept of home design, architecture and mechanical designing process. This study connects all users of relevant concerns to an augmented reality's user-intensive design. The paper provides you with the existential complexity of how the AR can be implemented to enhance the work of architects and designers. The proposed application shows two types of reality, marker-less and more marker-based. The new feature of the project is that no expensive devices are required. It can be used easily through smartphones and tablets. This is a cost-effective solution that mainly reduces the overhead accosted daily by, mechanical designers, interior designers and architects. The software displays all the features that mechanical designers, interior designers and architects may need.